Environmental investment and valuation: a Keynesian (and Freudian) perspective. (7th July 2008) - Juniper, James
The objective of the article is to critically assess the approach taken by Basili (1994) and Vercelli (1994) towards the valuation of non-marketed environment assets. To this end, the article examines Keynes's approach to uncertainty and irrationality as influences over economic behaviour. Modern interpretations of these Keynesian insights, which have been influenced by neoclassical quantitative finance and psychological theories of decision-making, are then reviewed. A brief overview of how real options theory has been applied to the analysis of corporate investment sets the scene for a discussion of Basili and Vercelli's concept of the quasi-option values associated with the valuation of environmental assets. A 'destructive' critique is mounted against neoclassical approaches to valuation and the article concludes with a series of 'constructive' philosophical observations, drawing on Spinozian aspects of Whitehead's process philosophy.